FEATURES OF THE KNOWLEDGE MANAGEMENT SYSTEM AND ITS ROLE IN ENHANCING THE COMPETITIVENESS OF THE ORGANIZATION - KOVALOVA, Viktoriia; KIM, Oleksii; MASHKINA, Oleksandra; KNIAZIEVA, Polina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This paper examines the essential characteristics of knowledge management systems and their role in strengthening organizational competitiveness. Effective knowledge management enables companies to adapt to rapid changes, foster innovation, and improve overall efficiency. The study underscores that the ability to manage knowledge strategically can create sustainable competitive advantages, enhance decision-making processes, and improve organizational learning.The article provides a comprehensive review of several theoretical and practical models of knowledge management, including the SECI model by Nonaka and Takeuchi, the Cynefin framework by Snowden, and the Ba model, among others. Each model offers a unique approach to the processes of knowledge creation, conversion, and application within organizations. Moreover, the 4I framework highlights the critical stages of organizational learning, while the DIKW hierarchy describes the transformation of raw data into actionable wisdom. Wiig’s process model emphasizes the organizational levels of knowledge management, from individual to collective, ensuring efficient information flow and knowledge utilization.Key processes in knowledge management—knowledge creation, retention, dissemination, and application—are presented alongside practical tools for their implementation. The study highlights how organizations can leverage corporate memory and information systems to enhance innovation, streamline operations, and provide better customer service. It also explores the role of knowledge-oriented corporate culture in fostering collaboration and continuous improvement.
Keywords: management system; competitiveness; innovation; knowledge management models; business process efficiency; market adaptation; risk reduction